The olfactory thalamus: unanswered questions about the role of the mediodorsal thalamic nucleus in olfaction - Courtiol, Emmanuelle; Wilson, Donald A. (Frontiers in Neural Circuits, 2015)
The mediodorsal thalamic nucleus (MDT) is a higher order thalamic nucleus and its role in cognition is increasingly well established. Interestingly, components of the MDT also have a somewhat unique sensory function as they link primary olfactory cortex to orbitofrontal associative cortex. In fact, anatomical evidence firmly demonstrates that the MDT receives direct input from primary olfactory areas including the piriform cortex and has dense reciprocal connections with the orbitofrontal cortex. The functions of this olfactory pathway have been poorly explored but lesion, imaging, and electrophysiological studies suggest that these connections may be involved in olfactory processing including odor perception, discrimination, learning, and attention. However, many important questions regarding the MDT and olfaction remain unanswered. Our goal here is not only to briefly review the existing literature but also to highlight some of the remaining questions that need to be answered to better define the role(s) of the MDT in olfactory processing.